2020
DOI: 10.1074/jbc.ra120.015347
|View full text |Cite
|
Sign up to set email alerts
|

Neuroligin-2 dependent conformational activation of collybistin reconstituted in supported hybrid membranes

Abstract: The assembly of the postsynaptic transmitter sensing machinery at inhibitory nerve cell synapses requires the intimate interplay between cell adhesion proteins, scaffold and adaptor proteins, and γ-aminobutyric acid (GABA) or glycine receptors. We developed an in vitro membrane system to reconstitute this process, to identify the essential protein components, and to define their mechanism of action, with a specific focus on the mechanism by which the cytosolic C-terminus of the synaptic cell adhesion protein N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…Previous studies hypothesized that the intracellular cytosolic domain of NL2 (NL2 icd ) binds to the SH3 domain of CB, resulting in an open/active state capable of interacting with plasma membrane phosphoinositides (Poulopoulos et al, 2009; Schäfer et al, 2020; Soykan et al, 2014). In the presence of 100 µM NL2 icd the ⟨τ⟩ of CFP in the F1 DA -NL2 icd complex was 2.6 ± 0.02 ns (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies hypothesized that the intracellular cytosolic domain of NL2 (NL2 icd ) binds to the SH3 domain of CB, resulting in an open/active state capable of interacting with plasma membrane phosphoinositides (Poulopoulos et al, 2009; Schäfer et al, 2020; Soykan et al, 2014). In the presence of 100 µM NL2 icd the ⟨τ⟩ of CFP in the F1 DA -NL2 icd complex was 2.6 ± 0.02 ns (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…ARHGEF9 encodes the protein Cb, which is an important organizer at inhibitory synapses [ 24 26 ], known to interact with the α2 subunit of GABA A R’s [ 29 ] among other inhibitory synaptic proteins [ 28 ]. Our previous work has shown that 13 amino acids within the large intracellular loop of α2 interacts with the Cb SH3 domain with micromolar affinity [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…The ARHGEF9 gene encodes a protein known as collybistin (Cb), which is a guanine nucleotide exchange factor (GEF) known to be an important organizer at synapses controlled by the neurotransmitters γ-amino butyric acid (GABA) and glycine [ 9 , 24 26 ]. Cb is known to interact with phosphoinositides via its plextrin homology (PH) domain [ 27 ], and the c-terminus of the adhesion molecule neuroligin-2 (NL2) via its Src homology (SH) 3 domain [ 28 ] (Fig. 1A ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous cell-based and biochemical studies documented that TC10 binding to CB triggers synaptic gephyrin clustering and enhances GABAergic neurotransmission ( Mayer et al, 2013 ; Kilisch et al, 2020 ). Moreover, prior work demonstrated that CB interaction with the intracellular domain of NL2 or Cdc42 leads to an open structure of CB, which favors its interaction with phosphoinositides located in the postsynaptic membrane ( Poulopoulos et al, 2009 ; Soykan et al, 2014 ; Schäfer et al, 2020 ). Our study with the wild-type mimicking CB FRET sensor (F1 DA ) ( Supplementary Figure 1A ) upon interaction with TC10 resulted in a significant increase in ⟨τ⟩ ( Figures 2A,B ), indicating a TC10-mediated CB opening.…”
Section: Discussionmentioning
confidence: 99%
“…The SH3 domain-deficient CB isoform (CB2-SH3 – ), on the contrary, adopts an open conformation, which possesses enhanced postsynaptic gephyrin-clustering and effectively replenishes the GTP-bound state of the small GTPase Cdc42 from its GDP-bound state ( Xiang et al, 2006 ; Reddy-Alla et al, 2010 ; Chiou et al, 2011 ; Tyagarajan et al, 2011 ; Soykan et al, 2014 ). Additionally, biochemical and cell-based studies suggested that amino-acid replacements weakening the inter-domain association of CB lead to an open/active CB conformation in which the DH domain is exposed ( Soykan et al, 2014 ; Schäfer et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%